SIMULASI NUMERIK ALIRAN FLUIDA PADA KINCIR AIR MENGGUNAKAN METODE SLIDING MESH INTERFACE - Agato, Agato; Deendarlianto, Deendarlianto; Indarto, Indarto; Alfeus Sunarso (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2024)
This research is aimed to investigate the accuracy and cost-effectiveness of numerical simulation method for the study of flow in a waterwheel system by comparing the results to the results of experiment, as well as by comparing the computational load of various solution schemes. The simulation is performed using Ansys Fluent with sliding mesh interface (SMI) method to treat the interface between rotating waterwheel region and static channel region. The governing equations are solved using the SIMPLE and Coupled schemes, and the effects of spatial and temporal resolutions are investigated. In general, the values of torque and power and the flow patterns obtained using numerical simulation are in a good agreement with those obtained using the experiment, which confirms the reliability of the simulation method. Considering the accuracy and computational load, it is recommended to use the Coupled scheme instead of the SIMPLE scheme for numerical simulation using SMI method.